Thermal stability of vegetal oils and fats by TG/DTG and DTA - Faria, E. A. de; Leles, MIG; Ionashiro, M.; Zuppa, T. D.; Antoniosi, N. R. (Editora Unesp, 2002)
Vegetal oils and fats are very useful in the food and chemist industry, they have demanded from researchers and technicians analytical methods able to estimate the conditions for their processing and storage. The thermal stability of vegetal oils is a main determinant in recognizing their value. The goal of this study is to evaluate the thermal stability of vegetable oils and fats extracted from the seeds of plants from Brazilian cerrado (araticum, babassu, Brazilian wine-palm, guariroba, and murici). The thermal stability was evaluated by TG/DTG and DTA techniques, in a temperature range from 30degreesC to 650degreesC, under nitrogen atmosphere, and at a heating rate 10degreesC min(-1). The TG/DTG and DTA used were efficient and fast in the determination of oils and fasts studied.
Keywords: vegetal oil; stability; thermal analysis